Comparative study of physiologic characteristics between the newly compiled Bafa Wubu of tai chi and 24 form simplified tai chi - Shaojun Lyu; Jianwei Zhang; Jianquan Nie; Cuihan Li; Tianming Gao; Wen Yuan; Zaihao Chen; Jing Ma (BMC, 2020)
Abstract Background The newly compiled Bafa Wubu of Tai Chi (Eight Methods and Five Footworks) is a fitness routine that has been developed in accordance with the appeal of the General Administration of Sport of China and promoted both in China and abroad. This paper aims to compare the differences in energy consumption and related parameters between the two types of Tai Chi. Methods A total of 60 healthy participants were recruited; 37 males (aged 37.4 ± 10.4 years) and 23 females (aged 31.9 ± 12.8 years). The maximal exercise capacity of participants was measured at baseline. Then, they received Tai Chi training for 12-week and their energy metabolism was measured dynamically. Results A set of the Bafa Wubu of Tai Chi requires approximately 3 min, while a set of 24 form simplified Tai Chi approximately 5 min and 40 s. The average oxygen uptake/kg (VO2/kg, 10.8 ± 2.52 ml/kg/min vs. 12.9 ± 2.59 ml/kg/min, P = 0.000), the highest VO2/kg (19.3 ± 6.03 ml/kg/min vs. 24.1 ± 7.50 ml/kg/min, p = 0.000, the average metabolic equivalent (METs,2.3 ± 0.16 METs vs. 3.2 ± 0.14 METs, p = 0.000), the highest oxygen pulse (VO2/HR, 11.1 ± 0.99 ml vs. 13.9 ± 0.93 ml, p = 0.000) and rate of perceived exertion (RPE, 10.7 ± 0.70 vs. 1.3 ± 0.62, p = 0.000) gained immediately after Bafa Wubu of Tai Chi exercise were significantly lower than those in 24 form simplified Tai Chi; heart rate recovery (HRR,1.5 ± 0.41 vs. 1.3 ± 0.45, p = 0.008) at 1 min after the practice was significantly higher than after the 24 form simplified Tai Chi. Meanwhile, the average heart rate (HR, 104.1 ± 11.41 bpm vs. 105.7 ± 9.68 bpm, p = 0.696) and the highest respiratory quotient (RQ, 1.0 ± 0.06 vs. 0.9 ± 0.09, p = 0.643) were not significantly different. The intensity of Tai Chi was described as the highest oxygen uptake of the participants when they performed the Tai Chi divided by their individual maximal oxygen uptake. Tai Chi intensity during Bafa Wubu of Tai Chi (50% ± 11.7% vs. 64% ± 12.5%) was significantly lower than during 24 form simplified Tai Chi. Conclusion The newly compiled Bafa Wubu of Tai Chi is characterized by lower energy consumption than 24 form simplified Tai Chi. Trial registration Ethics Committee of Sports Science Experiment, Beijing Sport University- 2018010H . Registered 19 June 2018